The Impact of Immune Cells, Metabolites, Inflammatory Factors, and Circulating Proteins on Atopic Dermatitis: Insights from a Mendelian Randomization Study - Zhou D; Gan G; Song S; Zi C; Bao Y; Hao W; Chen Q (Clinical, Cosmetic and Investigational Dermatology)
Dongqi Zhou,1 Gaofeng Gan,1 Shiwei Song,1 Cangyan Zi,1 Yichen Bao,1 Wenfeng Hao,1 Qiu Chen2 1Sichuan Taikang Hospital, Chengdu, Sichuan Province, 610213, People’s Republic of China; 2Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan Province, 610072, People’s Republic of ChinaCorrespondence: Qiu Chen, Email chenqiu1005@cdutcm.edu.cnBackground: The onset of atopic dermatitis (AD) is complex, and its specific pathological mechanisms have not yet been fully elucidated.Methods: Using circulating multi-omics as the exposure factors and AD as the outcome, we conducted univariable MR analysis. The circulating multi-omics data included immunomics (731 immune cell types), proteomics (4907 plasma proteins), metabolomics (1400 metabolites and 486 additional metabolites), and 91 inflammatory factors. MR analysis was conducted using IVW, WM, Simple Mode, Weighted Mode, and MR-Egger methods, with IVW as the primary analysis tool. To address horizontal pleiotropy, we utilized MR-Egger intercept tests and MR-PRESSO for correction, alongside the Cochrane Q statistic for heterogeneity assessment. Sensitivity analysis was performed using a leave-one-out strategy. To control for false positives due to multiple testing, we set a standard of a 5% false discovery rate. Additionally, we conducted F-statistics on the included SNPs to eliminate the impact of weak instrumental variables.Results: IL-18R1 on AD (OR = 1.12, 95% CI: 1.08– 1.17, PFDR < 0.01). Mannonate levels on AD (OR = 0.88, 95% CI: 0.83– 0.94, PFDR = 0.03). Retinol (Vitamin A) to linoleoyl-arachidonoyl-glycerol (18:2 to 20:4) on AD (OR = 1.12, 95% CI: 1.06– 1.18, PFDR = 0.03). HVEM on CM CD4+ cells on AD (OR = 0.81, 95% CI: 0.75– 0.88, PFDR < 0.01). CR2 on AD (OR = 0.81, 95% CI: 0.72– 0.90, PFDR = 0.04). MANSC1 on AD (OR = 0.87, 95% CI: 0.81– 0.93, PFDR = 0.04). IL18R1 (4097 inflammatory markers) on AD (OR = 1.11, 95% CI: 1.06– 1.17, PFDR = 0.01). HNRNPAB on AD (OR = 1.44, 95% CI: 1.23– 1.70, PFDR < 0.01).Conclusion: This study further explored the correlations between multi-omics data and AD. We identified seven previously unreported circulating substances with causal relationships to AD, filling a current theoretical gap.Keywords: multi-omics, immunomics, metabolomics, proteomics, Mendelian randomization, atopic dermatitis